The Accountant's Ethical Code of Conduct and Moral Reasoning from an Islamic Environment: Case in Yemen - Al-Aidaros, Al-Hasan Mohammed Hasan (2012)
An ethical code of conduct is developed to guide behaviors of members in or of organizations. Accountants, in this context, are not an exception. The availability of such ethical code of conduct is extremely important for both accountants and users of accounting information. However, currently in Yemen, there is no ethical code of conduct for Yemeni professional accountants. It is also equally important to know how Yemeni professional accountants perceive prescriptively and deliberatively on issues related to the ethical code of conduct. Hence, two phases of study were carried out to tap the issues. The first phase was sought to address the question of what constitutes the ethical code of conduct among Yemeni professional accountants. Data were collected from 386 users of accounting information in Yemen. The study employed interdependency analysis to reveal and confirm the domain of the accountants' ethical code of conduct. Results show that the ethical code of conduct consists of several ethical constructs. The second phase of the study was to know to what extent Yemeni professional accountants behave ethically at work. This is important because Islam emphasizes consistency between thought and action. Data were collected from 138 professional accountants in four main cities of Yemen i.e. Sana'a, Hadhramout, Taiz, and Aden. Results showed that Yemeni professional accountants exhibit higher level of moral reasoning beyond the conventional level. The findings of this study contribute to the body of knowledge by providing an Islamic perspective to the ethical issues which has similarities and differences vis-a-vis the Western perspective.